Factors Predicting COVID-19 Vaccine Effectiveness and Longevity of Humoral Immune Responses - Engin Berber; Ted M. Ross (Vaccines)
The COVID-19 pandemic, caused by SARS-CoV-2, prompted global efforts to develop vaccines to control the disease. Various vaccines, including mRNA (BNT162b2, mRNA-1273), adenoviral vector (ChAdOx1, Ad26.COV2.S), and inactivated virus platforms (BBIBP-CorV, CoronaVac), elicit high-titer, protective antibodies against the virus, but long-term antibody durability and effectiveness vary. The objective of this study is to elucidate the factors that influence vaccine effectiveness (VE) and the longevity of humoral immune responses to COVID-19 vaccines through a review of the relevant literature, including clinical and real-world studies. Here, we discuss the humoral immune response to different COVID-19 vaccines and identify factors influencing VE and antibody longevity. Despite initial robust immune responses, vaccine-induced immunity wanes over time, particularly with the emergence of variants, such as Delta and Omicron, that exhibit immune escape mechanisms. Additionally, the durability of the humoral immune responses elicited by different vaccine platforms, along with the identification of essential determinants of long-term protection—like pre-existing immunity, booster doses, hybrid immunity, and demographic factors—are critical for protecting against severe COVID-19. Booster vaccinations substantially restore neutralizing antibody levels, especially against immune-evasive variants, while individuals with hybrid immunity have a more durable and potent immune response. Importantly, comorbidities such as diabetes, cardiovascular disease, chronic kidney disease, and cancer significantly reduce the magnitude and longevity of vaccine-induced protection. Immunocompromised individuals, particularly those undergoing chemotherapy and those with hematologic malignancies, have diminished humoral responses and benefit disproportionately from booster vaccinations. Age and sex also influence immune responses, with older adults experiencing accelerated antibody decline and females generally exhibiting stronger humoral responses compared to males. Understanding the variables affecting immune protection is crucial to improving vaccine strategies and predicting VE and protection against COVID-19.